The detection of microbial DNA but not cultured bacteria is associated with increased mortality in patients with suspected sepsis—a prospective multi-centre European observational study. (March 2017) - O'Dwyer, M.J.; Starczewska, M.H.; Schrenzel, J.; Zacharowski, K.; Ecker, D.J.; Sampath, R.; Brealey, D.; Singer, M.; Libert, N.; Wilks, M.; Vincent, J.-L.
Abstract: Objectives: Blood culture results inadequately stratify the mortality risk in critically ill patients with sepsis. We sought to establish the prognostic significance of the presence of microbial DNA in the bloodstream of patients hospitalized with suspected sepsis. Methods: We analysed the data collected during the Rapid Diagnosis of Infections in the Critically Ill (RADICAL) study, which compared a novel culture-independent PCR/electrospray ionization-mass spectrometry (ESI-MS) assay with standard microbiological testing. Patients were eligible for the study if they had suspected sepsis and were either hospitalized or were referred to one of nine intensive care units from six European countries. The blood specimen for PCR/ESI-MS assay was taken along with initial blood culture taken for clinical indications. Results: Of the 616 patients recruited to the RADICAL study, 439 patients had data on outcome, results of the blood culture and PCR/ESI-MS assay available for analysis. Positive blood culture and PCR/ESI-MSI result was found in 13% (56/439) and 40% (177/439) of patients, respectively. Either a positive blood culture (p 0.01) or a positive PCR/ESI-MS (p 0.005) was associated with higher SOFA scores on enrolment to the study. There was no difference in 28-day mortality observed in patients who had either positive or negative blood cultures (35% versus 32%, p 0.74). However, in patients with a positive PCR/ESI-MS assay, mortality was significantly higher in comparison to those with a negative result (42% versus 26%, p 0.001). Conclusions: Presence of microbial DNA in patients with suspected sepsis might define a patient group at higher risk of death.